Prevalence of soil-transmitted helminths infection and associated risk factors among residents of Jigjiga town, Somali region, Eastern Ethiopia. - Abdlmenur Alewi Sedo; Ahmed Zeynudin; Tariku Belay; Mekdes Mekonen Belay; Ahmed Mohammed Ibrahim; Mohamed Omar Osman; Ramadan Budul Yusuf; Abdifatah Abdulahi (PLoS ONE)
Background One of the tropical illnesses that is often overlooked is soil-transmitted helminths, or STHs. In tropical and subtropical nations, where poor sanitation and contaminated water sources are common, they mostly impact the most vulnerable populations. Objective The aim of this study was to ascertain the prevalence of STHs and related risk factors among the people living in Jigjiga town, Somali region, Eastern Ethiopia. Methods A community-based cross-sectional study was revealed from June 1 to July 21, 2023. Study participants were selected through a multistage sampling method, where households were randomly chosen from the kebeles. A semi-structured questionnaire and observational checklist were used to collect some of the data. A stool sample was collected from each participant, and a single Kato-Katz was performed to detect STHs. Bivariate and multivariate logistic regression analyses were performed, and statistical significance was declared at a level of p-value < 0.05 between the outcome and independent variables. Results There were 507 participants in this study, and 90.9% of them responded. STH prevalence was 11.4% overall (95% CI =  9.0, 14.0). With a prevalent parasite species, A. lumbricoides was 9.3%, T. trichiura was 2.8%, and hookworms were 0.2%. Of the overall positive cases, 93.1% are due to single parasite infections. Independent predictors of STHs included low wealth status (AOR =  3.10; 95% CI =  1.25, 7.75; p =  0.015), infrequent hand washing before meals (AOR =  3.19; 95% CI =  1.55, 6.57; p =  0.002), earthen floors (AOR =  2.32; 95% CI =  1.12, 4.79; p =  0.023), and no drinking water treatment habit (AOR =  5.07; 95% CI =  1.89, 13.57; p =  0.001). Conclusion Jigjiga town had a low prevalence of STHs infections. Infrequent hand washing habits before meals, earthen floors, low wealth status, and no habit of treating drinking water were significant associated factors. Health education on handwashing, regular deworming, improved access to clean water and sanitation facilities to reduce the burden of STH effectively.